Breeding grain mold resistant sorghum cultivars - Reddy, B.; Bandyopadhyay, Ranajit; Ramaiah, B.; Ortíz, R. (2000)
Sorghum (Sorghum bicolor(L.) Moench) is the fifth important cereal crop after wheat (Triticum aestivumL.), maize (Zea maysL.), rice (Oryza sativaL.), and barley (Hordeum vulgareL.) in the world. It is cultivated in about 46 million ha with a total production of 62 million t (FAO 1998). Asia and Africa account 86% of the total area under sorghum, but their contribution towards total production is only 58% (FAO 1998). Nearly 90% of sorghum is grown in rainy season while postrainy season sorghum in India accounts for the remaining area. Sorghum grain yield potential is high. However, there is a gap of about 3 t ha-1in yield between research station yield trials and farmers' fields in India (AICSIP 1994). This reduction in the realized grain yield at farm level is due to several abiotic and biotic constraints. Grain mold is an important biotic constraint of sorghum and seriously compromises the grain yield and quality grains obtainable from improved cultivars. Grain mold occurs throughout the humid tropical and subtropical climates particularly when improved, short-and medium-duration cultivars that mature before the end of the rains are grown (Bandyopadhyay et al. 1988). It is caused by several non-specialized fungi. These include: Fusarium monliforme Sheld., Fusarium pallidoroseum (Cooke) Sacc.,Curvularia lunata (Wakker) Boedijnand Phoma sorghina (Sacc.) Boerema, Dorenbosch, & van Kesteren (Bandyopadhyay et al. 1988, 1998).Major efforts in breeding for grain mold resistance at the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), and other places in India as well as USA have met with partial success in breeding together high resistance levels of grain mold and grain yield. Annual global losses due to grain molds have been estimated at US$ 130 million (ICRISAT 1992).We have summarized in this paper the current efforts in breeding for resistance to grain mold with emphasis on ICRISAT work and outlined the future prospects.